Onset for Active Swimming of Microorganisms to Shape Their Transport in Turbulent Open Channel Flows - Zi Wu; Li Zeng; Guangmiao Li; Zheng Gong; Jie Zhan; Weiquan Jiang; Mengzhen Xu; Xudong Fu (Water Resources Research)
Abstract Research on active particles has primarily focused on transport in relatively weak flows, during which their active swimming plays a significant role. However, in natural or manmade waterways, the ambient flow velocity and water depth can be on the order of approximately 1 m/s and 1 m, respectively, generating turbulent diffusion that may be strong enough to potentially dominate the transport process, so that the active swimming might be negligible. In this paper, we propose a theoretical framework aiming at identifying the threshold at which the effects of active swimming become significant, under conditions of insufficient data for motion statistics of swimmers. While deriving the governing equation, we find that only the vertical component of the mean swimming has the potential to significantly influence the transport process. This manifests as the characteristic of inducing a non‐uniform vertical concentration distribution, in competition with the mechanism of turbulent diffusion, which leads to a uniform distribution. We obtain the analytical solution for the vertical concentration distribution, with the key dimensionless parameter α representing the interplay between the active swimming and turbulent diffusion. The threshold is found to be approximately at the order of magnitude of α ∼ 0.1, below which active swimming is considered negligible. The theoretical predictions are validated by numerical simulations employing Direct Numerical Simulation and particle tracking methods. Applying the theory to two types of microorganisms transported under different flow conditions suggests that there are typical scenarios where the active swimming is negligible, and the swimmers can be treated as passive particles.